2019
DOI: 10.1016/j.eneco.2019.104522
|View full text |Cite
|
Sign up to set email alerts
|

Towards flexible energy demand – Preferences for dynamic contracts, services and emissions reductions

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 57 publications
1
29
0
Order By: Relevance
“…Respondents require a lower overall compensation (WTA is negative) for accepting a control of their washing machine, no compensation for the control of their dishwasher (insignificant) but an additional compensation for the control of their freezer or dryer (WTA is positive). In general, studies outside of Germany (e.g., [12,15]) found that consumers dislike a control of their electricity consumption but these studies do not differentiate between appliances. For Germany, Dütschke and Paetz [17] discovered that households prefer an automated electricity control over a manual one.…”
Section: Estimation Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Respondents require a lower overall compensation (WTA is negative) for accepting a control of their washing machine, no compensation for the control of their dishwasher (insignificant) but an additional compensation for the control of their freezer or dryer (WTA is positive). In general, studies outside of Germany (e.g., [12,15]) found that consumers dislike a control of their electricity consumption but these studies do not differentiate between appliances. For Germany, Dütschke and Paetz [17] discovered that households prefer an automated electricity control over a manual one.…”
Section: Estimation Resultsmentioning
confidence: 99%
“…Finally, Ruokamo et al [15] combined in a CE dynamic tariffs with information on CO 2 -emission reductions. Their online-survey is based on responses of about 380 Finnish homeowners.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In this setting, the cost and benefit of volatility and flexibility are not internalized but socialized across all heat pumps. A more innovative tariff design, such as real-time pricing, would be needed to incentivize the choice of system-friendly heat pump systems and the provision of flexibility (Ruokamo et al, 2019). Moreover, retail prices include taxes, levies, and grid charges.…”
Section: Discussion and Limitationsmentioning
confidence: 99%
“…For example, a Finnish 30-year bond yield has been below 0.5% since the summer of 2019. Second, households may put weight on other factors related to PV systems, such as emissions reductions (Crago and Chernyakhovskiy, 2017;Ruokamo et al, 2019). To assess this point, we analysed how solar power output reduces households' CO 2 emissions of electricity consumption (see Fig.…”
Section: The Pv Investment Profitability Under Tou and Optimized Hot Water Heating Strategiesmentioning
confidence: 99%